Intra‐strain Variability in the Effects of Temperature on UV‐B Sensitivity of Cyanobacteria1. (14th October 2018) - Islam, Md Ashraful; Beardall, John; Cook, Perran
Abstract: Stratospheric ozone depletion is mostly marked over the Antarctic and to a lesser extent over the Arctic, though recent reports have revealed that this also occurs at lower latitudes. Continued depletion of ozone in the lower stratosphere allows more UVR to reach the Earth's surface. Furthermore, it is projected that surface water temperatures will increase by between 0.2 and 2.0°C by the year 2060 and this will directly or indirectly influence algal growth. The interactions between environmental factors are complicated by the existence of different strains (ecotypes) of the same species that may respond differently. To understand the interactive effects of temperature and UV‐B on two strains of Anabaena circinalis, we investigated the damaging effects of UV‐B on cell numbers and photosynthetic characteristics and also examined the effect of temperature on the capacity of cells to recover from such stress. Both strains of A. circinalis responded differently in terms of survival, photosynthetic characteristics and recovery with interactions between temperature and UV‐B. This could be due to the variations in strain‐specific photoreactive mechanisms. This needs to be explored further including more strains and species before definitive conclusions can be reached about effects of global change on cyanobacteria generally. Abstract : Increased temperature affects the responses of the cyanobacterium Anabeana circinalis to acute exposure to UV‐B. However, there are significant differences between strains in terms of survival and photosynthetic characteristics. Elevated temperature improved survival of strain CS537 under UV‐B but greatly increased the UV‐B sensitivity of CS541. The different responses shown by the two strains complicates predictions about global change impacts on cyanobacterial performance if these are based on experiments on single strains of species.